KAJIAN ETNOSAINS PROSES PRODUKSI GARAM TAMBAK DI DESA RAGUNG SAMPANG SEBAGAI PENDUKUNG MATERI PEMBELAJARAN IPA - Nufus, Ainun; Yasir, Mochammad; Sidik, Rahmad Fajar; Hadi, Wiwin Puspita; Yamin, Yamin; Wahyuni, Eva Ari (Natural Science Education Research, 2023)
This research aims to conduct an ethnoscience study of the salt pond production process in Ragung Sampang Village as a support for Science subject learning material. This study employs a qualitative descriptive approach. The research was carried out in Ragung Sampang Village using purposive sampling technique, which involves selecting informants, in this case, the salt farmers. Research instruments include interviews, observation sheets, and questionnaires. Data collection techniques encompass observation, interviews, documentation, and validation sheets. The findings are as follows: 1) There is a congruence between the ethnoscience study results of the salt production process and scientific principles. 2) The relationship between the results of the ethnoscience study of the salt production process and the scientific concepts found indicates alignment or correspondence with the Science learning concepts. During this study, a teaching module was produced as an outcome. The average validation scores from experts are as follows: Expert validation of content: 81%, Interview guide validation: 42%, Observation instrument validation: 60% and Media expert validation: 84%.